Upper Pliocene-Lower Pleistocene Upper Molasse Belorechensk Formation of Western Ciscaucasia in Context of Regional Neotectonics and Paleogeography - Trikhunkov, Ya. I.; Bachmanov, D. M.; Tesakov, A. S.; Titov, V. V.; Lomov, V. S.; Sokolov, S. A.; Nikolskaya, P. P. (Pleiades Publishing Ltd, 2024)
Molasses of foredeeps are important indicators of the newest orogenic uplifts, as well as the source of data on climate and landscape changes. One of the fullest sections of Neogene-Quaternary deposits is studied in valleys of the Belaya, Pshekha, and Psekups rivers at the junction of the Western and Northwestern Caucasus with the Eastern Kuban and Western Kuban foredeeps. The formation of the deposits corresponds to the main evolution stages of the Great Caucasus orogen, as well as the foredeeps. A summary of extensive published and original tectonostratigraphic materials has shown that the lowland and then hilly relief in an axial zone of Western Caucasus existed at least from the Middle Miocene. At the same time, the northern flank of the present-day orogen and the foredeeps were located at sea level and were repeatedly flooded by the seas up to the Kuyalnikian (Piacenzian-Gelasian) time, and the Western Kuban Foredeep was flooded even later. The main data on stratigraphy of the upper molasses and Pliocene-Quaternary tectonic movements of the region are based on facies analysis and bio- and magnetostratigraphic studies of the Upper Pliocene-Lower Pleistocene Belorechensk Formation. Its sedimentation started at the beginning of the Kuyalnikian as a result of an increase in the energy of mountain rivers due to the uplift of the riverheads. It is stated that the minimum average rate of uplift of the Western Caucasus in the basin of the Belaya River is 0.8 mm/year over last 4 mln years with acceleration up to 1.7 mm/year from the beginning of the Calabrian. The Belorechensk Formation includes three subformations, which successively become coarser clastic and correspond to the main stages of the accumulation of upper molasses in the Late Pliocene and Early Pleistocene during the intensification of uplifts and landscape-climate changes of Western Caucasus and Ciscaucasia.
Keywords: Ciscaucasian Foredeep; Western Caucasus; Adygean Ledge; Belorechensk Formation; molasses; neotectonics; stratigraphy; magnetostratigraphy; biostratigraphy; paleogeography